Recent advances in the synthesis of azaphenalene alkaloids: first enantioselective approaches. Issue 37 (31st August 2018) - Alujas-Burgos, Sílvia; Bayón, Pau; Figueredo, Marta
Abstract : This review provides an update of the synthetic progress towards azaphenalene alkaloids, including the pioneering enantioselective approaches. Abstract : Azaphenalene alkaloids are biosynthesised and segregated by diverse insects of the Coccinellidae family (ladybirds) and are believed to play an important role in the defensive mechanism against their natural predators. The particular unique framework of these alkaloids, along with their potential in the field of biological pest control, has led to several research groups developing synthetic sequences to prepare these compounds. The main purpose of the present review is to provide an update of the more recent synthetic progress towards these alkaloids, including the pioneering enantioselective approaches to chiral congeners.